Permanent Exhibit, Main Stream of 20th Century Art. (Toyama : Museum of Modern Art, 1989)
Magritte, René ; Delvaux, Paul ; Miró, Joan ; Fautrier, Jean ; Hartung, Hans ; Soulages, Pierre ; Poliakoff, Serge ; Pollock, Jackson ; Francis, Sam ; Yamaguchi, Takeo ; Sugai, Kumi ; Murai, Masanari ; Vasarely, Victor ; Riley, Bridget ; Calder, Alexander ; Rauschenberg, Robert ; etc.
Text English-Japanese
boek